Lymphoid and epithelial markers in small cell anaplastic thyroid tumours. Issue 8 (August 1985) - Burt, A D; Kerr, D J; Brown, I L; Boyle, P
Abstract : The expression of the lymphoid marker, common leucocyte antigen and of the epithelial marker, epithelial membrane antigen by small cell anaplastic thyroid tumours was studied in 53 tumours, using the peroxidase--antiperoxidase and avidin--biotin techniques. Common leucocyte antigen was found in 33 of the 53 tumours; six tumours were positive for epithelial membrane antigen; and the remaining 14 tumours were negative for both markers. These results support the suggestion that most small cell anaplastic thyroid tumours are of lymphoid origin. Survival data for patients with tumours positive for common leucocyte antigen showed a significantly better prognosis than did the data for patients with small cell tumours that did not express this marker (p less than 0.02).